There should be 24 turtles
Use the rules of logarithms and the rules of exponents.
... ln(ab) = ln(a) + ln(b)
... e^ln(a) = a
... (a^b)·(a^c) = a^(b+c)
_____
1) Use the second rule and take the antilog.
... e^ln(x) = x = e^(5.6 + ln(7.5))
... x = (e^5.6)·(e^ln(7.5)) . . . . . . use the rule of exponents
... x = 7.5·e^5.6 . . . . . . . . . . . . use the second rule of logarithms
... x ≈ 2028.2 . . . . . . . . . . . . . use your calculator (could do this after the 1st step)
2) Similar to the previous problem, except base-10 logs are involved.
... x = 10^(5.6 -log(7.5)) . . . . . take the antilog. Could evaluate now.
... = (1/7.5)·10^5.6 . . . . . . . . . . of course, 10^(-log(7.5)) = 7.5^-1 = 1/7.5
... x ≈ 53,080.96
Answer:
This ratio is 0.6.
Step-by-step explanation:
This ratio is:
gold 37.5%
-------- = ----------- = -0.6
nickel 62.5%
The difference in Elevation is 280
Answer:
6 - 5d is an expression equivalent to -5d + 6 using the commutative Property of Addition.
Step-by-step explanation:
Commutative Property of Addition
We know that we can add two numbers in any order.
For example,
Let 'a' and 'b' be two numbers.
We can add 'a' and 'b' numbers in any order, such as
a + b = b + a
Thus,
a + b = b + a is represented using the commutative Property of Addition.
In our case,
-5d + 6 can be written or represented using the commutative Property of Addition, such as
-5d + 6 = 6 - 5d
It is clear that -5d + 6 can be written in any order such as 6 - 5d.
In other words, 6 - 5d is an expression equivalent to -5d + 6 using the commutative Property of Addition.
Therefore, 6 - 5d is an expression equivalent to -5d + 6 using the commutative Property of Addition.